Ação protetiva da hexametilenoimina e do hidróxido de tetraetilamônio na dessilicação da zeólita ZSM-12 - Alencar Júnior, Nehemias Rodrigues de (2018)
The zeolites, crystalline aluminosilicates exhibiting micropore ordered networks (typically 0.3-1 nm), are important heterogeneous catalysts in a number of hydrocarbon conversions, such as cracking, hidro-isomerização, alkylation, esterification and oxidation. However, it is widely acknowledged that zeolitic catalysts suffer from intracrystalline diffusion limitations due to the molecular dimensions of micropores. As a result, intense efforts were concentrated on the synthesis of new or modified zeolites with better accessibility, mainly by pore enlargement. Thus, the hierarchical zeolites perform the task by coupling micropores with a mesoporous auxiliary network of intracrystalline nature. The synthesis ZSM-12 zeolite was also analyzed via conventional methodology (hydrothermal) at 150 ºC, with hexamethyleneimine (HMI) as the guiding agent of a greenhouse structure agitated for 7 days. The Post-synthesis methods to obtain zeolites ZSM-12 mesoporous were carried out through an alkaline treatment, in other words, desilication of a new variant from the desilication involving the leaching of NaOH in the presence of the structural drivers: the hexamethyleneimine (HMI) and tetraethylammonium hidroxide (TEAOH), which are added to preserve the volume of micropores and size of the mesopore in zeolite ZSM-12 hierarchical, acting as protective agents. The zeolites were characterized by x-ray diffractometry (DRX), adsorption physical of N2, thermal analysis (TG/DTG), ammonia desorption at programmed temperature (TPD) and scanning electron microscopy (SEM). These samples were also evaluated using the n-hexane cracking model reaction. The desilicated sample without the presence of protective agents obtained a higher increase in mesopore generation, maintaining the level of acidity similar to the samples treated with addition of HMI and TEAOH, but it presented inferior catalytic activity.